Beyond an All-Weather Friendship: Charting a "Shared Future for Mankind" in China-Pakistan Relations - Adam Saud, (ASIAN Journal of International Peace & Security (AJIPS), 2025)
This article explores the evolving trajectory of China–Pakistan relations through the lens of President Xi Jinping’s vision of a “community with a shared future for mankind.” Anchored in Constructivism and Liberal Institutionalism, the study examines how shared norms, mutual trust, and institutionalized cooperation shape bilateral ties beyond material interests. The article adopts a descriptive-analytical methodology, utilizing primary sources such as official policy statements and speeches, along with secondary scholarly and policy literature. It highlights the China-Pakistan Economic Corridor (CPEC) as a flagship mechanism of the Belt and Road Initiative (BRI), fostering connectivity, energy security, and socio-economic development in Pakistan while providing China with strategic trade routes. The analysis emphasizes the partnership’s significance in addressing non-traditional security challenges, which include food security, climate change, and regional stability. By examining historical milestones, ongoing projects, and future cooperation plans, the article demonstrates that the China–Pakistan relationship has entered into a new era of cooperation to become a model of mutually beneficial collaboration. It argues that the deepening of political trust, economic development, regional integration, and people to people contacts between the two states represents a practical manifestation of the shared future concept, offering lessons for global multilateralism and cooperative security in an era of shifting power dynamics.